Spectral shapes of second-forbidden single-transition nonunique β decays assessed using the nuclear shell model - Ramalho, Marlom; Suhonen, Jouni; Neacsu, Andrei; Stoica, Sabin (Frontiers in Physics, 2024)
Experimental and theoretical studies of β electrons (electrons emitted in β−-decay transitions) and their β-electron spectra have recently experienced a rapid expansion. These β spectral shapes have been used to study total β spectra of fission-product nuclei in the quest for explanation of the reactor-flux anomalies, and individual β transitions in search for β spectral shapes sensitive to the effective value of the weak axial coupling gA. In the former case the TAGS (total absorption gamma-ray spectroscopy) can be efficiently used to measure the total β spectral shapes and in the latter case dedicated measurements of the involved forbidden nonunique β transitions have been deployed. The fourth-forbidden nonunique decay transitions 113Cd(1/2g.s.+)→113In(9/2g.s.+) and 115In(9/2g.s.+)→115Sn(1/2g.s.+) represent theoretically and experimentally much-studied cases where the total β spectra consist of these single transitions. In these particular cases the TAGS method could be used to assess the effective value of gA. In the present work we have identified five more interesting cases where a total β spectrum consists of a single transition. These spectra correspond to second-forbidden nonunique transitions and are gA and/or sNME dependent, where sNME denotes the so-called small relativistic vector nuclear matrix element. These studies have been performed using the nuclear shell model with well established effective Hamiltonians. With this we target to β transitions that would potentially be of high interest for the TAGS and present and future dedicated β-spectrum experiments.